Ethikbegründungen zwischen Universalismus und Relativismus - Engelhard, Kristina; Heidemann, Dietmar H. (De Gruyter, 2012)
Biographical note: Kristina Engelhard,Universität Köln;Dietmar Heidemann,UniversitätKöln.
Description based upon print version of record
Keywords: Electronic books; Aufsatzsammlung; Ethik